2023
DOI: 10.1021/acssuschemeng.2c07479
|View full text |Cite
|
Sign up to set email alerts
|

Self-Growing MZIF8/GDE Bonding by N–Zn–O Boosts Electrochemical Oxygen Reduction to H2O2

Abstract: The two-electron oxygen reduction reaction (2e– ORR) is an environmentally friendly approach to the production of H2O2. Self-growing gas diffusion electrodes offer a lot of advantages like reduction of adhesive use, and lower electron and mass transfer resistance. However, MOF self-growing gas diffusion electrodes are rarely used for the production of hydrogen peroxide. Herein, a self-growing hydrophobic composite gas diffusion electrode has been proposed, consisting of densely distributed MZIF8 and graphite f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In addition, the higher content of Mo 3+ means the higher oxygen vacancy content. [29][30][31] Fig. 3d shows the highresolution O 1s spectra of MnO x /MnWO 4 @C-3 composites, which reveal three typical peaks at 530.87, 532.37 and 530.35 eV, representing lattice oxygen (O1), oxygen vacancy (O2) and oxygen species adsorbed on the surface (O3), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the higher content of Mo 3+ means the higher oxygen vacancy content. [29][30][31] Fig. 3d shows the highresolution O 1s spectra of MnO x /MnWO 4 @C-3 composites, which reveal three typical peaks at 530.87, 532.37 and 530.35 eV, representing lattice oxygen (O1), oxygen vacancy (O2) and oxygen species adsorbed on the surface (O3), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Wang et al 61 reported a MZIF8/graphite felt support (GF) composite (denoted as MGF) for the 2e-ORR using a microwave assisted route (Fig. 8(a)).…”
Section: Mof-based 2e-orr Electrocatalystsmentioning
confidence: 99%
“…9,10 A novel application of chemical looping, which has gained renewed interest, 11−15 is selective hydrogen combustion (SHC), in which hydrogen is selectively oxidized in a mixture of hydrocarbons. A strategy to surpass thermodynamic limitations in endothermic reactions, such as the catalytic dehydrogenation of ethylbenzene 12,16 or propane, 13 involves coupling of the dehydrogenation reaction with an exothermic SHC step to enable autothermal reactor operation.…”
Section: Introductionmentioning
confidence: 99%